EFEKTIVITAS KOMUNIKASI AKUN TIKTOK @BUIRAMIRA SEBAGAI MEDIA EDUKASI AKADEMIK MAHASISWA UNIVERSITAS RIAU - Tika Isma Hamida; Ringgo Eldapi Yozani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Tiktok is one type of social media that is not only effective for communicating, but also effectively used as an educational medium. One of the users using Tiktok as an educational medium is the tiktok account @buiramira, where the @buiramira tiktok account contains content about tips for dealing with college problems. This research uses a quantitative approach with descriptive type. The data in this study were obtained from questionnaires distributed online (google form). The population in this study were 29,470 Riau University students as of May 13, 2022. Then using the unknown populations formula, 135 samples were obtained. Furthermore, the sampling technique used in this study is accidental sampling. The results of this study indicate that the measurement of the communication effectiveness scale of the @buiramira tiktok account as an educational medium is obtained by an average of 3.53. This value is obtained from the calculation of the communication effectiveness variable according to Cutlip which consists of seven measurement indicators, namely the Credibility indicator with a value of 3.57 and is included in the very effective scale, Context (context) with a value of 3.59 and is included in the very effective scale. , Content (content) with a value of 3.54 and included in the very effective scale, Clarity (clarity) with a value of 3.50 and included in the very effective scale, Continuity and Consistency (Continuity and Consistency) with a value of 3.44 and included in the scale very effective, Channel (Channel) with a value of 3.62 and included in the very effective scale, Capability of The Audience (Capabilities or Audience Ability) with a value of 3.51 and included in the very effective scale. Keywords : Communication Effectivity, Education, Tiktok